2009
DOI: 10.1055/s-0029-1208092
|View full text |Cite
|
Sign up to set email alerts
|

Schwangerschaft und Reisen

Abstract: The second trimester is the safest time for travelling, because the pregnant woman feels generally most at ease and the risk of spontaneous abortion and pre-term labour is very low. Possible risks must be discussed with the obstetrician before travelling. If the pregnancy is uncomplicated most airlines allow flying up to the 36th (domestic flights) and 35th (international flights) week of gestation. Unless the fetal oxygen supply is already impaired at ground level due to an underlying disease, flying does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Chloroquine is safe during pregnancy, as confirmed by its long use and by a randomized, double-blind, placebo-controlled trial in pregnant Karen women that demonstrated that weekly chloroquine prophylaxis is safe for foetus and prevents P. vivax episodes [125]. Mefloquine is safe in the second half of pregnancy [126] and some authors recommend mefloquine use in high risk areas [127]. A post-marketing surveillance study evaluated the teratogenic potential of mefloquine in 1627 pregnant women, concluding that the risk wasn’t different from the risk observed in the general population [128].…”
Section: Risk Groupsmentioning
confidence: 99%
“…Chloroquine is safe during pregnancy, as confirmed by its long use and by a randomized, double-blind, placebo-controlled trial in pregnant Karen women that demonstrated that weekly chloroquine prophylaxis is safe for foetus and prevents P. vivax episodes [125]. Mefloquine is safe in the second half of pregnancy [126] and some authors recommend mefloquine use in high risk areas [127]. A post-marketing surveillance study evaluated the teratogenic potential of mefloquine in 1627 pregnant women, concluding that the risk wasn’t different from the risk observed in the general population [128].…”
Section: Risk Groupsmentioning
confidence: 99%